2012
DOI: 10.1292/jvms.11-0171
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal <i>Tritrichomonas suis </i>(=<i>T. foetus</i>) Infection in Japanese Cats

Abstract: abstract. Tritrichomonas suis (=T. foetus) has recently been reported to be a causative agent of chronic large-bowel diarrhea in cats. While the disease was previously attributed to Pentatrichomonas hominis, the etiologic agent for feline trichomonal diarrhea was identified as T. suis. Although feline trichomonosis due to T. suis has been reported at prevalences ranging from 14 to 31% in Europe and the U.S., no reports of the pathogen have been published to date in Japan. In 2008, however, we encountered a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Twenty-two of these samples were from nursery pigs (<4-months-old) and 8 were from fattening pigs. Fecal samples were examined by the fecal direct smear technique under a light microscope (BH-2, Olympus, Tokyo, Japan), and all 30 samples were applied to cultivation on Trichomonas Medium ® (Oxoid, Cambridge, U.K.) as described previously [5]. Giemsa staining of positive-culture smears was performed for morphological observations of trophozoites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two of these samples were from nursery pigs (<4-months-old) and 8 were from fattening pigs. Fecal samples were examined by the fecal direct smear technique under a light microscope (BH-2, Olympus, Tokyo, Japan), and all 30 samples were applied to cultivation on Trichomonas Medium ® (Oxoid, Cambridge, U.K.) as described previously [5]. Giemsa staining of positive-culture smears was performed for morphological observations of trophozoites.…”
Section: Methodsmentioning
confidence: 99%
“…Control measures have been successful in Japan, and no cases of bovine infection have been reported for more than 40 years. However, we previously reported that T. suis infection has occurred in cats in Japan with a prevalence rate of 8.8% [5]. Furthermore, although a T. suis infection was reported in pigs 2 decades ago in Japan [15], species identification in the paper was based on morphological methods.…”
mentioning
confidence: 99%
“…The sensitivity of direct examination of feces showed a much lower T. foetus diagnosis than the PCR, as highlighted in previous studies (Gookin et al 2004, Holliday et al 2009, Miró et al 2011, Tysnes et al 2011). Molecular diagnosis is a good choice mainly in the absence of viable organisms in fecal samples, reducing the false negative diagnosis (Holliday et al 2009, Doi et al 2012, Tysnes et al 2011) and even the false positive diagnosis using other methods such as direct examination of feces and cultivation (Miró et al 2011). According to the literature, it is difficult to differentiate T. foetus from the Pentatrichomonas Detection of natural occurrence of Tritrichomonas foetus in cats in Araçatuba, São Paulo, Brazil hominis, a commensal trichomonad of cats, especially by direct examination of feces (Gookin et al 2007, Yao & Kӧster 2015.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in several countries such as United Kingdom (Gunn-Moore et al 2007), The United States of America (Stockdale et al 2009), Switzerland (Frey et al 2009), Italy (Holliday et al 2009), Australia (Bell et al 2010), South Korea (Lim et al 2010), New Zealand (Kingsbury et al 2010), Greece (Xenoulis et al 2010), Germany (Kuehner et al 2011), Spain (Miró et al 2011), Norway (Tysnes et al 2011), Japan (Doi et al 2012), Canada (Hosein et al 2013) and France (Profizi et al 2013). Due to the increasing interest in this protozoan in feline medicine, the current study was designed to investigate the occurrence of T. foetus in Brazilian cats using direct examination of feces, PCR, and further genetic sequencing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation